Discursive rules and moral norms - Damiani, Alberto Mario (Revista de Filosofía, 2016)
The aim of this paper is to explain the connection between discursive rules and moral norms in the frame of discourse ethics. The paper begins with an analysis of the difference between action and operation and with a reconstruction of the concept of discourse. After that, the difference and the relationship between law and obligation are presented. The conclusion is that the connection between action and possible discourse is implicit in the notion of moral responsibility.